2015
DOI: 10.1038/bcj.2015.71
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with an increased risk of vertebral fracture in monoclonal gammopathies of undetermined significance

Abstract: Monoclonal gammopathies of undetermined significance (MGUS) have been shown to be associated with an increased risk of fractures. This study describes prospectively the bone status of MGUS patients and determines the factors associated with vertebral fracture. We included prospectively 201 patients with MGUS, incidentally discovered, and with no known history of osteoporosis: mean age 66.6±12.5 years, 48.3% women, 51.7% immunoglobulin G (IgG), 33.3% IgM and 10.4% IgA. Light chain was kappa in 64.2% patients. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 33 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…This is consistent with earlier findings that have shown a higher relative risk of fractures in men with MGUS than in women, 4 and that men with MGUS have an unexpected high prevalence of vertebral fractures. 32 In postmenopausal women, the generally enhanced rate of bone loss may mask the effect of MGUS on bone metabolism. 22 Further analysis on the MGUS individuals who developed fractures showed Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with earlier findings that have shown a higher relative risk of fractures in men with MGUS than in women, 4 and that men with MGUS have an unexpected high prevalence of vertebral fractures. 32 In postmenopausal women, the generally enhanced rate of bone loss may mask the effect of MGUS on bone metabolism. 22 Further analysis on the MGUS individuals who developed fractures showed Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…The search identified 184 non duplicate potentially eligible studies. After excluding 164 papers through title and abstract review and 10 from full text examination, 10 studies [10][11][12][13][14][15][16][17][18][19] were included ( Supplementary Figure 1). 6…”
Section: Resultsmentioning
confidence: 99%
“…Four studies [12][13][14][15] reported an overall prevalence of fractures of 14% (95%CI: 3-52) in MGUS participants, while the prevalence of osteoporosis in 3 studies [12,13,19] was 14% (95%CI:2-62) ( Supplementary Figures 1-2). Table 1, BMD (lumbar spine, hip and femoral neck) and T-scores (lumbar spine and hip) were not different between MGUS and controls.…”
Section: Cross-sectional Bone Health Outcomesmentioning
confidence: 99%
“…In retrospective studies, MGUS is associated with a 6 times greater risk of vertebral fracture and 1.4–2.5 times greater risk of any fracture when compared to control populations ( 11 , 18 ). Limited prospective evaluations of skeletal abnormalities in MGUS have been completed to date, but those that have confirm the high prevalence of vertebral fractures in MGUS and suggest an association between non-traumatic vertebral fractures and a clonal lambda light chain predominance ( 19 ). MGUS and SMM are associated with osteopenia, altered bone microstructure, and an increased rate of bone resorption and overall fracture risk ( 11 , 12 , 20 ).…”
Section: Pathophysiology Of Myeloma Bone Diseasementioning
confidence: 99%